The impact of agricultural price policy in developing countries - J. A. Mollett (Intereconomics, 1988)
Agricultural price policies are under closer review now in many developing countries. There is a growing tendency to rely more on market forces. What impact have agricultural price policies had on the performance of the agricultural sector in developing countries until now?
Keywords: 330; Agriculture